Global functionality and associated factors in the older adults followed by Home Care in Primary Health Care - Mariane Lurdes Predebon; Gilmara Ramos; Fernanda Laís Fengler Dal Pizzol; Naiana Oliveira dos Santos; Lisiane Manganelli Girardi Paskulin; Idiane Rosset (Universidade de São Paulo, 2021)
Objective: to analyze the association of global functionality with the main functional systems and the sociodemographic variables of older adults followed by Home Care in Primary Health Care. Method: a cross-sectional study with 124 older people developed through home interviews. Functionality was assessed by Basic Activities of Daily Living (Barthel) and Instrumental Activities of Daily Living (Lawton and Brody); the main functional systems were assessed using the Mini-Mental State Exam, by the Timed Up and Go test, by the Geriatric Depression Scale (15 items), and questionnaire with sociodemographic variables. Bivariate and multivariate analyses were applied (Poisson Regression). Results: 46% of the older adults showed moderate/severe/total dependence for basic activities and instrumental activities had a median of 12. In the multivariate analysis, there was an association between moderate/severe/total dependence on basic activities with cognitive decline (p=0.021) and bedridden/wheelchair users (p=0.014). Regarding the dependence on instrumental activities, there was an association with age ≥80 years (p=0.006), single/divorced marital status (p=0.013), cognitive decline (p=0.001), bedridden/wheelchair (p=0.020), and Timed Up and Go ≥20 seconds (p=0.048). Conclusion: the decline in cognitive and mobility was associated with poor functionality in basic and instrumental activities. The findings highlight the need to monitor Home Care for these individuals and serve as guidelines for health actions.